(untitled) - John, Maggie Jo St. (New York, 1994)
Designed to help develop reading and familiarization skills in the particular work area of advertising, this book contains passages and exercises, and is accompanied by an answer key and an audio cassette. The book is divided into units, each of which addresses different aspects of advertising and which offers a range of activities, including pre-reading, and text and organization, comprehension and vocabulary questions for which a separate answer key is provided. The passages in the book are taken from books, magazines and newspapers dealing with advertising matters and therefore offer authentic vocabulary and idiom.
Keywords: English language,Readers; Business english,Advertising